Pengaruh Reward Terhadap Kinerja Karyawan Maskapai Citilink Indonesia Di Bandar Udara Yogyakarta Internasional Airport - Razif Pamungkas; Maria Valeria Roellyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
As part of the system factor, reward (reward) is an important element to create high employee performance. Reward (reward) is one way used to motivate someone to do good and work achievements or performance. This study aims to find out whether the provision of rewards to employees at Citilink companies affects the performance of Citilink employees at Yogyakarta International Airport and how much influence the provision of rewards has on employee performance at Citilink Yogyakarta International Airport. Quantitative research was employed in this study. Questionnaires are sent in order to collect data. All Citilink Indonesia Airlines personnel at Yogyakarta International Airport comprised the population under study, totaling 20, and 20 persons made up the sample because the population was under 100. Data analysis techniques use instrument tests, namely validity tests, and reliability tests, as well as hypothesis tests, namely Simple Linear Regression, T Test, and Determination coefficient test. A significant value for the partial effect of X on Y is 0.008 < 0.05 and with the results of the t table and t value calculated, then 2.955 > 2.10092, it can be concluded that there is an effect of giving rewards on the performance of Citilink Airlines employees at Yogyakarta International Airport. This study found a relationship between the provision of rewards and employee performance. The partial effect of Variable X on Variable Y (0.327 R Square) is 32.7%, with additional factors not included in this research influencing the other portions.